Yellow Fever: It worth a review in the current epidemiological context - Miguel Ángel Serra Valdés (Medisur, 2017)
Infectious emergent and re-emergent diseases constitute a challenge in this century for all nations. The Republic of Angola, with which we have a close relation of friendship and collaboration, is immersed in a clear epidemic of yellow fever. We have in common the transmitting vector. The objective of the present review is to update of the medical personnel and those in training, in undergraduate and postgraduate stages so as to alert about the danger yellow fever represents which is one of the oldest infectious diseases identified in the old and new worlds. An updated review was realized about its ethio- pathogenic, clinical manifestations, epidemiology, diagnosis, treatment and prevention. Epidemiological vigilance in the international present context is necessary at all moments and in all places of the country. If there is a delay in the diagnosis, it shall contribute substantially to the possibility of its introduction in the territory and an epidemiologic outbreak.